2017
DOI: 10.21608/adjg.2017.5263
|View full text |Cite
|
Sign up to set email alerts
|

Remineralization Potential of Grape Seed Versus Amorphous Calciumphosphate-Nanoparticles on Sound and Caries Affected Dentin

Abstract: Objectives: This study was conducted to evaluate the remineralization potential of grape seed extract versus amorphous calcium phosphate nanoparticles on sound and caries affected dentin. Materials and methods: Grape seed extract powder (GSE) was added to Clearfil SE primer with a concentration of 0.5 wt% to obtain primer + GSE while nanoparticles of amorphous calcium phosphate (NACP) were incorporated into the Clearfil SE adhesive at mass fractions of 20% to obtain adhesive + NACP. Class V cavity preparation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…On the other hand, GSE showed the highest percentage increase in dentine radiodensity, this was in accordance with other studies (7,(20)(21)(22) . Which showed that, 6.5% GSE solution increased dentin mechanical properties, microhardness and tensile strength.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, GSE showed the highest percentage increase in dentine radiodensity, this was in accordance with other studies (7,(20)(21)(22) . Which showed that, 6.5% GSE solution increased dentin mechanical properties, microhardness and tensile strength.…”
Section: Discussionsupporting
confidence: 92%
“…Escribano-Bailon and co-workers 34 Some studies have evaluated the effect of GSE on demineralized dentin 36,29 , but the effect of this agent on the remineralization of enamel defects is not well understood. Using grape seed extract, Alrafee et al 37 could produce remineralization of sound and carious affected dentin of white rabbits. Silva APP et al 38 found that grape seed extract could inhibit demineralization of artificial carious lesions in extracted bovine central incisors, though in a smaller scale compered to fluoride.…”
Section: Groupsmentioning
confidence: 99%
“…Preparation of artificial caries-affected dentin On each rabbit, the left side prepared cavities on the upper and lower teeth were etched using 37% phosphoric acid (Meta Biomed, Germany) for 30 s followed by rinsing for 30 s to obtain artificial caries-affected dentin (Alrafee et al 2017).…”
Section: In Vivo Studymentioning
confidence: 99%